A Proposal to Ease the Heavy Burden of Domestic Labour - Murat Aybars Tunca (İstanbul Hukuk Mecmuası)
Domestic labour, a well-known form of unpaid labour, is widespread throughout many countries. Most domestic labour is performed mostly by housewives. Housewives often face uncertainty about their future because of a lack of adequate social security, regular income, and retirement plans. As a functional tool for transforming society, law plays a role in changing such social inequalities. In this article, we discuss how law can offer remedies to fix domestic labour problems. Drawing on feminist standpoint theory, this article explores how scientific methods can contribute to understanding and redressing domestic labour problems with to-the-point regulations. Feminist Standpoint Theory asserts that knowledge is socially situated. It contends that marginalised groups, such as women, are uniquely aware of social and political issues because of their lived experiences. According to this theory, research should begin from the standpoint of these marginalised individuals. By doing so, biases can be addressed, and a more just society can be achieved. In essence, it challenges the traditional objectivity of scientific research and emphasises the importance of diverse perspectives. In this context, this article discusses the significance of evidence-influenced policies in addressing women’s problems. While doing so, we will present the progress of Türkiye with examples of its efforts to tackle gender inequalities. The article acknowledges opposition from the men’s right movement, which seeks to reverse advancements in women’s rights in Türkiye. However, it argues that their arguments are ideological rather than based on evidence, particularly regarding property division laws. In this article, we focus on the matrimonial property regime, which is one of the many negative contributors to the problems of the performers of domestic labour. As a remedy, we propose amendments to the Civil Code.